PA01.01. A clinical study on the effect of paneeya kshara in the management of asmari w.s.r. to urinary calculi - Chakradhar, K V (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: In Ayurveda, the diseases asmari was described under asta maha gada by Susrutha. This shows how difficult this disease to treat medically or surgically. According to modern science, various deposits of urological salts precipitate and form the calculi. The prevalence of these disease urinary calculi is about 3% of population with 1% of highly exploitable with severe agony and complications. The management in contemporary modern science is toughest approach because it may solve the problem temporarily but cannot render preventing or recurrence. Hence there is need to evaluate a better remedy. Here the kshara described by susrutha is selected and the yava kshara is chosen for study. METHOD: Total of 10 patients was selected from the SV ayurvedic college, Tirupati after subjecting to selection criteria based on inclusion and exclusion criteria. These 10 patients are given with yava kshara as paneeya kshara with the dose of 250 mg once in week for 4 weeks. The observations are noted and results were assessed on the basis of subjective (scoring prepared for symptomatology for pain, burning micturition, dysuria, tenderness in renal angle, haematuria, microscopic analysis of urine) and objective (kub usg) parameters. And then they are subjected for statistical validity. RESULT: It is found to be the yava kshara (paneeya kshara) is effective reducing the symptoms and producing remarkable benefit to patient. CONCLUSION: Even though it is difficult to treat the disease asmari, the yava kshara shown significant result and definitely be simple to use and cost effective management.